Sejarah Uang, Fungsi, Dan Perannya Dalam Perkembangan Ekonomi Menurut Para Pakar Ekonomi Syariah - Ritonga, Miftahul Janna; S, Syahpawi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This article explores in depth the concept of money from the perspective of Islamic economics, focusing on its historical background, functions, and strategic role in economic development according to the thoughts of prominent Islamic scholars such as Imam Al-Ghazali, Ibn Khaldun, and Ibn Taymiyah. The study reveals that in Islam, money is not regarded as a commodity, but as a medium of exchange, a unit of account, and a store of value that must be used productively to achieve social justice and economic balance. Through a qualitative approach and literature study, it was found that practices such as usury (riba), hoarding (ikhtikar), and speculation are strictly prohibited as they contradict the values of Sharia. The classical thoughts of these scholars remain highly relevant as a foundation for developing an Islamic financial system that is just, ethical, and sustainable in the modern era. This study offers a conceptual contribution to the advancement of Sharia-based monetary policy and strengthens the understanding that Islamic economics is not only free from riba but also oriented toward the welfare of society.